Dissecting Dynamic and Hydration Contributions to Sequence-Dependent DNA Minor Groove Recognition - Ha, Van L.T. (Biophys J, 2020)
Sequence selectivity is a critical attribute of DNA-binding ligands and underlines the need for detailed molecular descriptions of binding in representative sequence contexts. We investigated the binding and volumetric properties of DB1976, a model bis(benzimidazole)-selenophene diamidine compound with emerging therapeutic potential in acute myeloid leukemia, debilitating fibroses, and obesity-related liver dysfunction. To sample the scope of cognate DB1976 target sites, we evaluated three dodecameric duplexes spanning >10(3)-fold in binding affinity. The attendant changes in partial molar volumes varied substantially, but not in step with binding affinity, suggesting distinct modes of interactions in these complexes. Specifically, whereas optimal binding was associated with loss of hydration water, low-affinity binding released more hydration water. Explicit-atom molecular dynamics simulations showed that minor groove binding perturbed the conformational dynamics and hydration at the termini and interior of the DNA in a sequence-dependent manner. The impact of these distinct local dynamics on hydration was experimentally validated by domain-specific interrogation of hydration with salt, which probed the charged axial surfaces of oligomeric DNA preferentially over the uncharged termini. Minor groove recognition by DB1976, therefore, generates dynamically distinct domains that can make favorable contributions to hydration release in both high- and low-affinity binding. Because ligand binding at internal sites of DNA oligomers modulates dynamics at the termini, the results suggest both short- and long-range dynamic effects along the DNA target that can influence their effectiveness as low-MW competitors of protein binding.